Migracja zarobkowa Ukraińców - Padura, Nataliia (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
Examining this theme we ran into a global problem, as migration of labour force, foremost it should be noted that migratory motions are the so-called «indicator» of reaction of population on changing in the economic, political, social washing of any society. A size, directions and scales of such processes of certain, is testified a measure to stability or vice versa about instability of community development. The process of labour migration in Ukraine has a tendency to growth. It is for this reason necessary for more effective it follows to inculcate the use of labour resources system of monitoring of migratory streams of population and to perfect the legislative providing but other. As stopping labour migration is impossible, it costs to use it positive consequences and to try to decrease negative.
Keywords: Ukraińcy; migracja zarobkowa